2001
DOI: 10.1136/ip.7.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of hospitalized farm injuries in Canada

Abstract: CAISP is a new agricultural injury surveillance program in Canada. Data from this system are actively used to inform prevention initiatives, and to indicate priorities for etiological and experimental research in the Canadian agricultural setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
2
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 16 publications
(15 reference statements)
4
56
2
3
Order By: Relevance
“…This result is not consistent with several previous studies, which have found elevated injury probabilities either for the young (Geller et al, 1990;Carstensen et al, 1995;Zhao et al, 1995;MacCrawford et al, 1998;Gerberich et al, 2001) or for the old (Erlich et al, 1993;Zhao et al, 1995;Gerberich et al, 1998;Pickett et al, 2001). The lack of very young and old operators in the study sample might be at least a partial explanation.…”
Section: Discussioncontrasting
confidence: 97%
“…This result is not consistent with several previous studies, which have found elevated injury probabilities either for the young (Geller et al, 1990;Carstensen et al, 1995;Zhao et al, 1995;MacCrawford et al, 1998;Gerberich et al, 2001) or for the old (Erlich et al, 1993;Zhao et al, 1995;Gerberich et al, 1998;Pickett et al, 2001). The lack of very young and old operators in the study sample might be at least a partial explanation.…”
Section: Discussioncontrasting
confidence: 97%
“…Farm children experience high rates of premature death, 2-4 morbidity, 5,6 and disability 7 attributable to injury. Children account for ϳ19% of all agricultural injury fatalities and hospitalizations.…”
mentioning
confidence: 99%
“…10 Many pediatric farm injuries occur because children are exposed to specific occupational hazards. 2,6 There are 3 main approaches to the protection of children from workplace injuries: (1) occupational health and safety regulations; (2) modifications of the work environment (eg, engineering controls); and (3) education about known hazards.…”
mentioning
confidence: 99%
“…In order to determine the characteristics of the labor accident the average of sex, age, injured body part, reason for accident, the values of working hours in which the accident took place has been taken for the years 2003-2005 in order to establish the characteristics of work accidents and they are compared as agricultural and other sectors (Harker et al 1991, McCurdy and Carroll 2000, Myers 1998, Pickett et al1995, Pickett et al 2001, Solomon 2002, Von Essen and McCurdy 1998.…”
Section: Methodsmentioning
confidence: 99%
“…This value is 313 and 1500 in the other sectors respectively. In the calculation carried out in this way, it is seen that the women working in agricultural sector is under risk 2.2 times more than the women working in non-agricultural sector similarly, In their study, Pickett et al (2001), has determined that the rate of men is greater in injured cases because of agricultural machines in the rate of 1 to 9 and in injured cases without machines in the rate of 1 to 3. Dimich et al (2004) has determined that the men are exposed to work accidents 9 times more.…”
Section: Gendermentioning
confidence: 97%